Analisa selang kelahiran harapan dan sebenarnya terhadap paritas di Kota Malang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
ABSTRACT The analysis of relationship between ideal birth interval (IKI) and actual birth interval (KS) toward mean parity in this survey which was conducted in the city of Malang (by using simple random sampling with nr.321), has show positive support to the encouragement of having three years or more birth interval. The finding shows that there are significant difference between IKI and IKS and also the 110 has reduced the effect. of IKS toward parity, beside IKI has consistent positive correlation toward mean parity. Therefore, the BKKBINPF, encouragement for having three years or more birth interval should be more announced, otherwise the mean parity will affected.